2017
DOI: 10.1101/221754
|View full text |Cite
Preprint
|
Sign up to set email alerts
|

Targeted Genotyping of Variable Number Tandem Repeats with adVNTR

Abstract: Whole Genome Sequencing is increasingly used to identify Mendelian variants in clinical pipelines. These pipelines focus on single nucleotide variants (SNVs) and also structural variants, while ignoring more complex repeat sequence variants. We consider the problem of genotyping Variable Number Tandem Repeats (VNTRs), composed of inexact tandem duplications of short (6-100bp) repeating units. VNTRs span 3% of the human genome, are frequently present in coding regions, and have been implicated in multiple Mende… Show more

Help me understand this report
View published versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
27
0

Year Published

2018
2018
2022
2022

Publication Types

Select...
5
4

Relationship

6
3

Authors

Journals

citations
Cited by 17 publications
(27 citation statements)
references
References 60 publications
0
27
0
Order By: Relevance
“…Over the last several years, we and others have developed a series of tools for genome-wide genotyping of STRs [12,44,16,23] from short reads or targeted genotyping of VNTRs [4] from both short and long reads. These tools primarily rely on identifying reads that completely enclose the repeat of interest.…”
Section: Introductionmentioning
confidence: 99%
“…Over the last several years, we and others have developed a series of tools for genome-wide genotyping of STRs [12,44,16,23] from short reads or targeted genotyping of VNTRs [4] from both short and long reads. These tools primarily rely on identifying reads that completely enclose the repeat of interest.…”
Section: Introductionmentioning
confidence: 99%
“…In addition, we parsed out SV loci according to regions with a single SV across the samples and those with multiple different SVs and identified that 38,239 (59%) of our SV calls occur as single, unique events in the respective region and the rest 26,869 (41%) occur in regions with one or more nearby SVs ( Figure S1 ) . Recent evidence suggests that a significant fraction of novel SVs could be tandem repeats with variable lengths across the population 30,31 and we found that 49% of the singleton unique SVs are completely within the UCSC Genome Browser Tandem Repeat (TR) tracks while 93% of the clustered unique SVs are within TR tracks. Because regions with multiple variants will pose additional complexities for SV genotyping that are beyond the scope of the current version of Paragraph, we limited our LRGT to the 9,238 deletions and 10,870 insertions that are not confounded by the presence of a different nearby or overlapping SV (see Methods ).…”
Section: Construction Of a Long Read-based Ground Truthmentioning
confidence: 65%
“…al. (2017) [29]. Briefly, VNTRTyper takes advantage of the long read sequencing to identify the number of repeat units in the TR regions.…”
Section: Methodsmentioning
confidence: 99%